Detection of Habitat Shifts of Cetacean Species: A Comparison Between 2010 and 2017 Habitat Suitability Conditions in the Northwest Atlantic Ocean - Chavez-Rosales, Samuel; Josephson, Elizabeth; Palka, Debra; Garrison, Lance (Frontiers in Marine Science, 2022)
The simultaneous effects of human activities in the ocean and climate changes have already produced a series of responses from the marine ecosystems. With the potential of more future human activities, such as offshore renewable energy developments, proactive management is required. To facilitate effective management and conservation actions, it is important to identify species at risk and critical habitats. Here we examine 16 cetacean species habitat suitability in the western North Atlantic Ocean, based on habitat models developed from dedicated sighting survey data collected by NOAA- Northeast and Southeast Fisheries Science Centers from 2010 to 2017. The models were based on observed species distribution as a function of 7 static physiographic characteristics and 14 dynamic environmental covariates. We compare species-specific core habitats between 2010 and 2017 and identified significant seasonal differences in patterns of habitat change across guilds. There was an average northward shift of 178 km for the species across the study area. The effects of these shifts are unknown, but for already stressed species the contraction or displacement of their historical habitat could exacerbate population declines. Therefore, the impending development of offshore regions and the effects of climate change stress the need of adaptively managing ecosystems facing multiple challenges.